PEMBERIAN WARISAN PADA SALAH SATU AHLI WARIS: PERSPEKTIF TAFSIR HERMENEUTIK AYAT WARIS - Agus Salim (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2022)
The flow of globalization not only affects people's attitudes, but also affects the development of science, technology development, and also affects changes in the social values ??of society. The value system referred to here is, in the past, in classical times, many people had a tendency to fight over inheritance, now the more prosperous people are, changing that perception. Some people today actually give inheritance to be waqf or even given to heirs who take care of their parents because the heirs who take care of their parents need it more or they find it more difficult to take care of their parents, so that in the view of other heirs, the heirs who care for Parents are more entitled to all inheritance. Giving inheritance to heirs who take care of parents seems contrary to the provisions of the Qur'anic verse which stipulates that inheritance must be divided according to the division determined by the Qur'an or determined by hadith. In this study, the researcher tries to re-examine the interpretation of the Qur'anic verses about inheritance verses by using a normative descriptive methodology and using a hermeneutic approach as a model of interpretation. This research is expected to be able to contribute to the thoughts of Islamic law which continue to experience changes both in the pattern of goals and or socioculture, especially the law that discusses al Mu'amalah al Insaniah.